Every Turn of the Wheel: Circular Time and Cordelia’s Revolt: from William Shakespeare to the British Enlightenment - Tadd Graham Fernée (English Studies at NBU, 2017)
This article argues that William Shakespeare's King Lear anticipates core political dynamics of the English Civil War (1641-49), and philosophical tenets of the British Enlightenment in John Locke and David Hume. It analyzes three principle and competing paradigms of public authority in King Lear: theodicy, nature, and the autonomy of thought. The play is historically contextualized within the 16th century. King Lear, moreover, portends revolutionary new thought patterns: the centerless universe of modern astronomy, and human embeddedness in fluid nature without fixed identity. Three variants on the concept of "nothing" - existential, social, and philosophical - interweave the cosmic and political threads, based on a circular temporality. Shakespeare's character, Cordelia, affirms the everyday over the cosmic, and the sociological over the metaphysical. King Lear depicts a profound moral trans-valuation in early modern history, whose shifting temporal horizons remain central also to contemporary politics.